2020
DOI: 10.1371/journal.pone.0238532
|View full text |Cite
|
Sign up to set email alerts
|

The potential antimalarial efficacy of hemocompatible silver nanoparticles from Artemisia species against P. falciparum parasite

Abstract: Malaria represents one of the most common infectious diseases which becoming an impellent public health problem worldwide. Antimalarial classical medications include quininebased drugs, like chloroquine, and artesunate, a derivative of artemisinin, a molecule found in the plant Artemisia annua. Such therapeutics are very effective but show heavy side effects like drug resistance. In this study, "green" silver nanoparticles (AgNPs) have been prepared from two Artemisia species (A. abrotanum and A. arborescens),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 52 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Their optical, biological characteristics, and high electrical conductivity can be highlighted [2]. The AgNPs proved to be useful in industrial and health products, such as coating of medical devices [23], biosensors [24], in bio-imaging [25], as antibacterial [8], antifungal [26], antiparasitic [27], antiviral [28], anticancer agents [29], and as drug carriers [30], among other applications. Silver nanoparticles have been extensively studied and recognized as useful tools in therapeutics [22], since they have a high surface/volume ratio, ease of synthesis, tunable surface chemistry and surface functionalization, and good penetration and traceability in the organism.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Their optical, biological characteristics, and high electrical conductivity can be highlighted [2]. The AgNPs proved to be useful in industrial and health products, such as coating of medical devices [23], biosensors [24], in bio-imaging [25], as antibacterial [8], antifungal [26], antiparasitic [27], antiviral [28], anticancer agents [29], and as drug carriers [30], among other applications. Silver nanoparticles have been extensively studied and recognized as useful tools in therapeutics [22], since they have a high surface/volume ratio, ease of synthesis, tunable surface chemistry and surface functionalization, and good penetration and traceability in the organism.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…A good way to do this is to control the pH of the solution in which the nanoparticles are synthesized, knowing that in general higher pH corresponds to smaller particles [25]. Consequently, a procedure already in use was modified to control the dimension of the AgNPs by tuning the pH in solution [26]. Hence, three different batches of Artemisia-AgNPs have been prepared at distinct pH values (7, 8, and 9) in order to examine whether, as expected, the pH change was able to modify their size, but also to influence their capping and, therefore, their biological behavior.…”
Section: Nanoparticles Characterization and Xtt Analysismentioning
confidence: 99%
“…measured IC 50 of different silver nanoparticles. The results demonstrated that A. abrotanum -AgNPs displayed better antiplasmodial effect considering 50%, 90% and 99% inhibition concentrations [ 68 ].…”
Section: New Directions Of Biological Activity Of Extracts From the Herb And/or Leaves And/or Essential Oil Confirmed By Scientific Reseamentioning
confidence: 99%